SOIL POLLUTION WITH HEAVY METALS AND BIOREMEDIATION METHODS - BOROZAN, Aurica Breica; MISCA, Corina Dana; MORAR, Adriana; OBISTIOIU, Diana; RABA, Diana Nicoleta; PIRVULESCU, Luminita; CABA, Ioan Ladislau; ALEXA, Ersilia; POIANA, Mariana Atena; BORDEAN, Despina Maria; PETCU, Carmen Daniela (Agrolife scientific journal, 2021)
The soil is a living and dynamic ecosystem permanently subject to anthropogenic pollution. Heavy metal pollution is a major factor of microbiota imbalances, and thus of severe soil degradation. The microbiota is represented by a wide range of microbial species that maintain and improve soil fertility by performing biogeochemical cycles in nature. Heavy metals are found naturally in the soil and play a key role in supporting microbial processes, but excess waste stored and neutralized improperly can be harmful, due to bioaccumulation along the trophic chain. Among the heavy metals commonly found in the soil are: lead (Pb), chromium (Cr), zinc (Zn), cadmium (Cd), copper (Cu), mercury (Hg), and nickel (Ni). The mobility of heavy metals in the environment, in general, and in the soil, in particular, is reduced, and therefore their contact with microorganisms is long and influences the structure of the microbial community. Existing studies emphasize the high bioaccumulation capacity of cadmium but also increased mobility affecting an entire trophic chain, and lead exerts an inhibitory effect on telluric microorganisms, even at very low concentrations. The overall activity of the soil, denitrifiers, and enzymes, is deeply affected by the presence of heavy metals. Their effect depends on the concentration and pH of the soil. Pedoclimatic factors can also contribute to these changes. Even in this situation, microorganisms can contribute to bioremediation and rendering the soil in the agricultural circuit. Among the bacterial genera that have developed mechanisms of resistance to certain heavy metals are Bacillus, Arthrobacter, Corynebacterium, Pseudomonas, Alcaligenes